The impact of monetary policy on inflation rates in Algeria is a record study during the period 1990-2017 - Zaitri, Sara; Chaban, Amer Said; Chouikat, Mohammed (Dirassat Journal Economic Issue, 2020)
This paper aims to study the impact of monetary policy on inflation in Algeria during the period 1990-2017, based on the methodology of cointegration, and through this study shows that the model variables are in the case of cointegration and this led us to estimate the correction model The results of the assessment were economically and statistically acceptable and the Monetary mass had a positive and significant effect on the inflation rates in Algeria during the period 1990-2017.